Power take-off selection for a fixed U-OWC wave power plant in the Mediterranean Sea: The case of Roccella Jonica. (15th January 2021) - Scialò, A.; Henriques, J.C.C.; Malara, G.; Falcão, A.F.O.; Gato, L.M.C.; Arena, F.
Abstract: This paper aims to maximize the performance of a U-type Oscillating Water Column power plant integrated into a breakwater to be built in Roccella Jonica, Mediterranean Sea, Italy. In this location, both prevalent mild waves and less frequent highly energetic sea states occur. The main challenge is to select a Power Take-Off (PTO) system able to operate with high-efficiency in this wave climate without the need of turning the power plant off for safety reasons. A non-linear time-domain wave-to wire model was developed to evaluate the performance of the Roccella Jonica power plant. Capture width ratio results for single and multi-stage Wells turbines were compared with the biradial turbine. The possibility to install a single turbine on combined air chambers was also considered to reduce the overall PTO costs. The rotational speed of the biradial turbine was found to only rarely exceed the maximum allowed limit during the most energetic sea states, while the Wells turbines too often exceeded that limit. The introduction of relief valves was found to be necessary to keep the PTO rotational speed within safety limits. Optimal turbine diameter, generator rated power and multi-chamber configuration were selected by maximizing the performance of the power plant. Highlights: Time-domain wave-to-wire model of the Roccella Jonica U-OWC power plant was developed. Results for single and multi-stage Wells turbines were compared with biradial turbine. Multi-chamber configurations were considered to reduce PTO costs. Relief valves were considered to keep turbine rotational speed within safety limits. The biradial turbine was found to be more efficient than the Wells turbines.